Pyrrolomycins as antimicrobial agents. Microwave-assisted organic synthesis and insights into their antimicrobial mechanism of action. Issue 5 (1st March 2019) - Raimondi, Maria Valeria; Listro, Roberta; Cusimano, Maria Grazia; La Franca, Mery; Faddetta, Teresa; Gallo, Giuseppe; Schillaci, Domenico; Collina, Simona; Leonchiks, Ainars; Barone, Giampaolo
Graphical abstract: 1d -SrtA Complex. SrtA Docking score: −6.4 kcal/mol. SrtA FRET IC50 : 140 µM. Biofilm Inhibition Formation of S. aureus ATCC 25923, IC50 : 3.4 nM. A three-fold reduced activity of a high-Mw S. aureus murein hydrolase. Highlights: Some pyrrolomycins have been selected to study their mechanism of action. Molecular modeling studies have been conducted on the target Sortase A. Enzymatic tests and assays on inhibition of staphylococcal biofilm formation and on murein hydrolase activity were performed. All compounds showed a good inhibitory activity toward Sortase A. Pyrrolomycin1d showed a good affinity in docking experiment to Sortase A and exhibited the highest capability to interfere with biofilm formation of S. aureus showing an IC50 of 3.4 nM. Abstract: New compounds able to counteract staphylococcal biofilm formation are needed. In this study we investigate the mechanism of action of pyrrolomycins, whose potential as antimicrobial agents has been demonstrated. We performed a new efficient and easy method to use microwave organic synthesis suitable for obtaining pyrrolomycins in good yields and in suitable amount for their in vitro in-depth investigation. We evaluate the inhibitory activity towards Sortase A (SrtA), a transpeptidase responsible for covalent anchoring in Gram-positive peptidoglycan of many surface proteins involved in adhesion and in biofilm formation. All compounds show a good inhibitory activity toward SrtA, having IC50 values ranging from 130 to 300 µM comparable to berberine hydrochloride. Of note compound1d shows a good affinity in docking experiment to SrtA and exhibits the highest capability to interfere with biofilm formation of S. aureus showing an IC50 of 3.4 nM. This compound is also effective in altering S. aureus murein hydrolase activity that is known to be responsible for degradation, turnover, and maturation of bacterial peptidoglycan and involved in the initial stages of S. aureus biofilm formation.